Comparing the Performance of Logit and Probit Early Warning Systems for Currency Crises in Emerging Market Economies - Fabio Comelli (Journal of Banking and Financial Economics)
We compare how logit (fi xed effects) and probit early warning systems (EWS) predict in-sample and out-of-sample currency crises in emerging markets (EMs). We look at episodes of currency crises that took place in 29 EMs between January 1995 and December 2012. Stronger real GDP growth rates and higher net foreign assets signifi cantly reduce the probability of experiencing a currency crisis, while high levels of credit to the private sector increase it. We fi nd that the logit and probit EWS out-of-sample performances are broadly similar, and that the EWS performance can be very sensitive both to the size of the estimation sample, and to the crisis defi nition employed. For macroeconomic policy purposes, we conclude that a currency crisis defi nition identifying more rather than less crisis episodes should be used, even if this may lead to the risk of issuing false alarms.